PC controlled function generator using direct digital synthesis (DDS) technology for electrical capacitance tomography - Abdul Rahim, Ruzairi; Teo, Chin Heng; Sulaiman, S.; Abdul Manaf, M. S. (Penerbit UTM Press, 2006)
A function generator is widely used for experimental work and testing to generate various types of waveform (sine, square, triangle, etc) with a particular frequency bandwidth. One of its applications is in generating waveform for the ECT (Electrical Capacitance Tomography) system. ECT is used to retrieve the details of material in a flow system. An economical PC Controlled Function Generator was designed for the use of waveform generating in ECT. For the ECT system, high accuracy and frequency waveforms are needed. Three basic waveforms are required; the sine wave, square wave, and triangular wave. The objective is to build a function generator which is capable of generating high accuracy waveforms with acceptable distortion and stability. An interfacing system between a PC and the function generator was also selected and developed with the purpose of producing accurate amplitude and frequency of the waveforms. This interfacing allows remote control to the function generator for a wider usage.